2020
DOI: 10.3390/sym12030397
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Magneto Hydro-Dynamics Effects on a Polymer Chain Transfer in Micro-Channel Using Dissipative Particle Dynamics Method

Abstract: In this paper, the effect of Magneto Hydro-Dynamics (MHD) on a polymer chain in the micro channel is studied by employing the Dissipative Particle Dynamics simulation (DPD) method. First, in a simple symmetric micro-channel, the results are evaluated and validated for different values of Hartmann (Ha) Number. The difference between the simulation and analytical solution is below 10%. Then, two types of polymer chain including short and long polymer chain are examined in the channel and the effective parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The effecting parameters involves zeta potential, electric field and kh parameter which the study of these parameter had been done in Refs. 23 27 . The accuracy of this method is less than 10% compared to analytical results 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effecting parameters involves zeta potential, electric field and kh parameter which the study of these parameter had been done in Refs. 23 27 . The accuracy of this method is less than 10% compared to analytical results 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, in order to study the flow simulation in more detail, researchers used non-continuous fluid methods to simulate these phenomena at the nanoscale in a simple channel 22 26 . The study of the effective parameters of electroosmotic flow is also one of the important topics that has been done in order to better understand this phenomenon 27 . Using the proper simulation method, for investigation of electroosmotic flow in nano scale, plays important role for finding details of movement of fluids and consequently transfer of a polymer chain through fluid flow 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the value of the Hartmann number increased, the velocity profile became flatter. The plug-like shape remained constant for a large portion of the channel width [46,47]. The current flowing in the closed loop generated a non-uniform 9 shows the variation of the velocity profile along the dimensionless width in the Y-axis imposed by the Lorentz force at the center of the magnetohydrodynamic pump.…”
Section: Magnetohydrodynamic Pump (Mhd) Performancementioning
confidence: 99%
“…Moreover, as the value of the Hartmann number increased, the velocity profile became flatter. The plug-like shape remained constant for a large portion of the channel width [46,47]. The current flowing in the closed loop generated a non-uniform negative small electromagnetic Lorentz force which counteracted the conducting fluid flow in the magnetic field creating a flat velocity boundary layer [45].…”
Section: Magnetohydrodynamic Pump (Mhd) Performancementioning
confidence: 99%
“…Some scholars have noticed that using soft material and power of fluid can pressurize bag or be evacuated for deflation, called origami-inspired artificial muscles [28], these mechanism are reported that can lift objects more than 1000 times more than own weights. To specify behavior of this component, simulation of inflation of AMF is carried out for the first time using dissipative particle dynamics (DPD) [39][40][41][42][43]. DPD is a particle based method for simulation of fluids especially in the case of interaction of fluid particles and membrane particles or polymer chain, this approach has been recently applied for this type of simulation.…”
Section: Dpd-numerical Simulation Of Ammentioning
confidence: 99%